2006
DOI: 10.1074/jbc.m600184200
|View full text |Cite
|
Sign up to set email alerts
|

NFAT Induces Breast Cancer Cell Invasion by Promoting the Induction of Cyclooxygenase-2

Abstract: The NFAT (nuclear factor of activated T cells) family of transcription factors plays a fundamental role in the transcriptional regulation of the immune response. However, NFATs are ubiquitously expressed, and recent evidence points to their important functions in human epithelial cells and carcinomas. Specifically, NFAT has been shown to be active in human breast and colon carcinoma cells and to promote their invasion through Matrigel. The mechanisms by which NFAT promotes invasion have not been defined. To id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
135
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 54 publications
(48 reference statements)
6
135
0
7
Order By: Relevance
“…NFAT has been involved in promoting breast and colon carcinoma motility and invasion through Matrigel, mediating integrin-dependent events (Jauliac et al, 2002;Chen and O'Connor, 2005). In a recent report, Yiu and Toker (2006) have shown in breast cancer cells that increased expression and activity of NFAT-induced Cox-2 expression and PGE 2 production, resulting in increased invasion that was reduced by inhibiting Cox-2 expression or activity (Yiu and Toker, 2006). Multiple evidences support the involvement of Cox-2-derived PGs in tumor progression by their ability to enhance migration and invasion of carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NFAT has been involved in promoting breast and colon carcinoma motility and invasion through Matrigel, mediating integrin-dependent events (Jauliac et al, 2002;Chen and O'Connor, 2005). In a recent report, Yiu and Toker (2006) have shown in breast cancer cells that increased expression and activity of NFAT-induced Cox-2 expression and PGE 2 production, resulting in increased invasion that was reduced by inhibiting Cox-2 expression or activity (Yiu and Toker, 2006). Multiple evidences support the involvement of Cox-2-derived PGs in tumor progression by their ability to enhance migration and invasion of carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, involvement of Gaq-coupled receptors as the GRP-R in the activation of NFAT and in the induction of NFATdependent genes has been described in a variety of cell types (Boss et al, 1996;Horsley and Pavlath, 2002;Liu et al, 2004). Noticeably, recent reports have proposed that NFAT proteins may play an important role in cancer, having shown a direct involvement of NFATmediated transcriptional regulation of different genes, including Cox-2 (Jauliac et al, 2002;Lara-Pezzi et al, 2002;Saurin et al, 2002;Neal and Clipstone, 2003;Holzmann et al, 2004;Yiu and Toker, 2006). As mentioned above, GRP-R and Cox-2 expression in human colon cancer cells correlates with more invasive characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…40 NFAT-1 was found to be amplified in pancreatic cancers 41 which could lead to the regulation of proinvasive genes, such as seen in breast carcinomas with NFAT-mediated upregulation of autotaxin. 42 Furthermore, NFAT-1 can also induce the expression of cyclooxygenase-2 43 which is known to be overexpressed in pancreatic tumors. 44 The association of the a6b4 integrin and known cooperating oncogenes such as Ras and c-Met and regulation of transcription factors, such as NFAT-1 in early tumor precursor lesions, suggests that integrin a6b4 could cooperate and/or activate these factors to drive the development and progression of pancreatic adenocarcinomas and contribute to the invasive and metastatic phenotype of these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypertonic saline has been reported to induce COX-2 in rat macrophages [87] and human ECs [88]. The participation of NFAT transcription factors in COX-2 activation was also already shown in several additional cell types [89][90][91][92][93][94]. In fact, previous research had shown that the angiogenic signaling involved in the induction of COX-2 by VEGF in human ECs requires the activation of NFAT proteins [91].…”
Section: Biophysical Pathways: the Role Of Hyperosmolar Stressmentioning
confidence: 97%